Pengolahan Sampah Organik di Pasar Landungsari sebagai Sumber Energi: Studi Proyek Biogas Berbasis Lingkungan - Rahmanisa, Nabila Nur; Ziah, Khalidah; Basya, Adib Mohamad Nafis; Razaq, Farhan Ahmadi (Maliki Interdisciplinary Journal, 2025)
The issue of organic waste in Landungsari Market, Malang, has caused negative impacts on the environment and public health. This article discusses an environmentally based organic waste processing project using anaerobic fermentation with EM4 to produce small-scale biogas. The project involved observation, experimentation, and community outreach. The results show that vegetable and fruit waste can be processed into methane gas and organic fertilizer, although gas production remains limited. The project’s success was reflected in the community’s enthusiasm and the potential of biogas as an environmentally friendly alternative energy source. Additionally, the project serves as an educational tool in Environmental Education (PLH). It is hoped that this initiative can be further developed with more efficient biodigesters and the use of animal manure to increase gas output. Thus, biogas production from waste can offer a sustainable solution to organic waste issues in markets and households.